Adjuvant radiotherapy and chemotherapy improve survival in patients with pancreatic adenocarcinoma receiving surgery: adjuvant chemotherapy alone is insufficient in the era of intensity modulation radiation therapy - Mao‐Chih Hsieh; Wei‐Wen Chang; Hsin‐Hsien Yu; Chang‐Yun Lu; Chia‐Lun Chang; Jyh‐Ming Chow; Shee‐Uan Chen; Yunfeng Cheng; Szu‐Yuan Wu (Cancer Medicine)
Abstract In the era of intensity modulation radiation therapy (IMRT), no prospective randomized trial has evaluated the efficacy of adjuvant therapies such as adjuvant concurrent chemoradiotherapy (CCRT), adjuvant sequential chemotherapy and radiotherapy (CT‐RT), and adjuvant CT alone in resectable pancreatic adenocarcinoma (PA). Through propensity score matching, we designed a nationwide, population‐based, head‐to‐head cohort study to determine the effects of dissimilar adjuvant treatments on resectable PA. We minimized the confounding of various adjuvant treatment outcomes among the following resectable PA groups of patients from the Taiwan Cancer Registry database: group 1, adjuvant CCRT; group 2, adjuvant sequential CT‐RT; and group 3, adjuvant CT alone. All the studied techniques are IMRTs. The matching process yielded a final cohort of 588 patients (196, 196, and 196 patients in groups 1, 2, and 3, respectively). In both univariate and multivariate Cox regression analyses, adjusted hazard ratios (aHRs; 95% confidence interval [CI]) of death derived for the adjuvant CCRT and adjuvant sequential CT‐RT cohorts compared with the adjuvant CT alone cohort were 0.398 (0.314–0.504) and 0.307 (0.235–0.402), respectively. A combination of adjuvant IMRT and CT for resectable PA treatment improves survival to a greater extent than does adjuvant CT alone.